Evaluation of discrete-time VSC on an inverted pendulum apparatus with additional dynamics - Hara, Masaaki; Furuta, Katsuhisa; Pan, Yaodong; Hoshino, Tasuku (Zielona Góra: Uniwersytet Zielonogórski)
Discrete-time Variable Structure Control (VSC) with sliding sector is experimentally evaluated on a new rotational-type inverted pendulum apparatus including an additional dynamics which is used to investigate the robustness of the controller. It is experimentally shown that the discrete-time VS controller makes the system robust stable with respect to parameter uncertainties and gives a quick response against external disturbances, which yields a good control performance without chattering.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka